Keeping an eye on the use of eye-lens weight as a universal indicator of age for European wild rabbits - Patricia H. Vaquerizas (Nature Portfolio, 2021)
Abstract Accurate methods for age determination are critical to the knowledge of wildlife populations' age structure and, therefore, to their successful management. The reliability of age estimation may have profound economic and ecological consequences on the management of the European wild rabbits, Oryctolagus cuniculus, in its native and introduced range, where it is a keystone species and a major pest, respectively. As in other mammal species, European rabbits' age is often estimated using the Gompertz relationship between age and lens' weight. The growth rate formula has been developed based on data collected from European rabbits introduced in Australia, where a single subspecies (O. cuniculus cuniculus, Occ) is present. However, this curve has never been validated in the species native range, the Iberian Peninsula, where two subspecies (Occ, and O. c. algirus, Oca) coexist naturally. In this study, we tested the relationship between age and lens' weight using 173 Occ and 112 Oca wild rabbits that were surveyed in two experimental facilities in Spain. Our findings show that, in the native range, the published growth curve formula fits well Occ but not Oca data. Therefore, we recommend using the formula reported in this study to estimate the age of Oca (Lens dry weight = 240 × 10(−64.9/(Age+32))). This study supports Oca rabbits' distinctiveness revealed by previous studies, which suggests that management interventions should be applied to protect this subspecies whose distribution range is very narrow and whose populations seem to be declining. More broadly, our findings point to the importance of testing the suitability of growth curves defined for other species with different genetic forms as occurs in the European wild rabbit case.